Bezpodstawne wzbogacenie w prawie i nauce jugosławiańskiej: [Unjust enrichment in Jugoslav law and science] (Studia Prawnicze / The Legal Studies, 1984)
The article deals with the classic institution of civil law - unjust enrichment. The work discusses: normative sources of unjust enrichment in Jugoslav law (art. art. 210-219 of the code of obligations of 1978), premises of claims to return (enrichment, impoverishment, mutual relation between them understood as, a genetic relation) and a lack of legal grounds, the scope and object of the obligation to return (settlement of accounts in connection with expenses, benefits, consequences of loss and damage of the object of enrichment), problems of faul prestation, prestation as a result of a null contract.Unjust enrichment in Jugoslavia has not a subsidiary character - concurrence of claims is admissible.A characteristic feature of the discussed institution in Jugoslavia (law and doctrine) is its specific instability: many important problems of unjust enrichment are solved ad hoc by courts, e.g. tours decide whether it is a necessary condition that the enrichment was still inherent in the. veurichee's property at the moment of claim (the principle of the enrichment's topicality), courts decide what happens to faul prestation (remaining of enrichment at the enrichee's, its return to the imporerished or forfeiture on behalf of the territorial unit, depending on the fact whether and which party of he contract had known that the exercising of the contract was an undue performance. Thus, Jugoslav approach is quite flexible, Which is a result of long tradition of praetor law in Jugoslavia where during the Post-war period, up till 1978, no statute law existed.